Effect of Fin Type on Frosting Characteristics of an Air-source Heat Pump - Huang Dong; Liu Xiaoyu; Wang Yanlu (Zhileng xuebao)
The effects of fin type of outdoor coil in an air-source heat pump unit on the dynamic frosting characteristics were experimentally investigated. The fins include the flat, wavy and wavy/slit type. The decreasing orders of both the average and maximum values of the heating capacity, COP and input power are flat, wavy and wavy/slit fins under the frosting condition. The average values of heating capacity, COP and input power for the wavy/slit fin are decreased by 14.57%, 8.26% and 7.11% respectively than those for the flat fin. The performance parameters for the wavy/slit fin decrease earliest and most greatly, then for the wavy fin, and finally for the flat fin. The frost has the advantage of enhancing the air-side heat transfer coefficient due to the phase change from vapor to frost. Meanwhile, it has the disadvantage of decreasing the fan airflow rate across the outdoor coil because the frost decreases the fin spacing and increases the air pressure drop. The curves of the performance parameters have the ascending and descending segments during the frosting period, which accords with the microcosmic growth characteristics of the frost. In the early stage of frosting cycle, the frost crystal grows from the grain shape to the column one which does not decrease the fin spacing remarkably, so the advantage of the frosting is greater than its disadvantage, which results in the ascending segment of performance. In the middle and final stages, the frost crystal grows along the radius direction, then stacks up between the frost columns, so the fin spacing is decreased remarkably and the disadvantage of the frosting is greater than its advantage.